Never marry a scandalous duke - Miller, Renee Ann (Miller, Renee Ann. Infamous lords series, 2022)
A thoroughly roguish nobleman and a devoted lady entomologist have absolutely nothing in common--or do they? Love is far from scientific when it truly blooms. Lady Sara Elsmere is far more concerned about her study of butterflies than society's gossip. Ian McAllister, the Duke of Dorcester, is perfectly satisfied to remain a rogue for the rest of his days. But when he finds he has kissed the wrong shepherdess, he's faced with a dilemma. Promising Sara the use of her dowry to fund her studies seals the pair's businesslike deal. But as they embark on their life together, they discover that their mutual attraction has sparked desire--and possibly deeper feelings--not easily tamed. Can their matrimonial experiment possibly end in real love? -- Adapted from back cover.